MANAJEMEN BERBASIS SEKOLAH DALAM UPAYA MENINGKATKAN PARTISIPASI ORANG TUA SISWA BIDANG SARANA DAN PRASARANA - Wartini, Sri; Komariah, Laili; Subagiyo, Lambang; Warman, Warman (STIT Ibnu Rusyd Tanah Grogot, 2025)
School-Based Management (SBM) is an approach that grants schools autonomy in managing educational processes and resources. One of the main challenges of SBM is the low level of parental participation, particularly in terms of facilities and infrastructure. Parental involvement is crucial for improving the quality of education and directly impacts the enhancement of school facilities. This article discusses the importance of parental participation in the development of school infrastructure, identifies the factors that influence parental involvement, and suggests strategies to increase their engagement. By building effective communication, educating parents about their roles in school development, and organizing social activities such as community service or fundraising events, schools can encourage greater parental involvement. Such initiatives not only improve school facilities but also strengthen the relationship between parents and the school community. Increased parental involvement in managing school resources ultimately leads to a more conducive learning environment, supporting the overall goal of enhancing students' educational experience. Through collaboration, schools can ensure sustainable progress in both educational quality and school infrastructure.